PENGARUH PROFESIONALISME AUDITOR TERHADAP KUALITAS KINERJA AUDITOR INTERNAL (Studi Empiris pada Internal Auditor PT. Sinar Himalaya) - Aminati, Diah (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research aim to examine the infuence of auditor professionalism onthe quality of intern auditor performance. The sample of this research are allauditors at pt.sinar himalaya -jakarta, surabaya, semarang, medan, pulogadung.The data is taken from questionaire which is shared to respondent. The usedvariable in this research is based on dependent variable and independentvariable. Variable independent is auditor profesionalism including auditorcompetency, auditor independency, auditor accountability, auditor workexperience, accountancy information system understanding while dependentvariable intern audit performance quality. The data is analyzed by using doublelinear regression analysis. The result of this research indicates that the auditorcompetency, auditor independency, auditor work experience and accountancyinformation system comprehension effects positively on intern audit performancequality, while auditor accountability variable doesnt have any effect on thequality of intern auditor performance.Key word : audite professionalism, competency, independency, accountability,work experience, SIA comprehension, intern audit performance quality